The Influence of EB-Irradiated Treatment on Enhancing Barrier Property and Crystallization Behavior of Rubber-Toughened Nanocomposites - N. A. Jamal; H. Anuar; A. R. Shamsul Bahri (Journal of Nanotechnology)
Electron beam (EB) irradiation technique was introduced to modify the crystallization and oxygen (O2) barrier properties of high density-polyethylene (HDPE)/ethylene propylene diene monomer (EPDM) matrix and HDPE/EPDM filled withorganophilic montmorillonite (OMMT). The absorbed dose for EB-irradiation was fixed at 100 kGy. HDPE/EPDM matrix and HDPE/EPDM filled with OMMT at 4 vol% loading were prepared via melt intercalation method. It was found that the barrier resistance of HDPE/EPDM filled withOMMT against oxygen (O2) transmission was significantly enhanced by EB-irradiation absorbed dose of 100 kGy as compared to the control system. The crystallization temperature, Tc, and melting temperature, Tm, were also improved with the addition of OMMT along with the aids of EB-irradiation technique. Field emission scanning electron microscope (FESEM) revealed that the stacking condition of OMMT particles was greatly reduced by EB-irradiation treatment as evidenced by finer surface and less formation of voids.